Gambaran Tingkat Pengetahuan Siswa Tentang Pertolongan Pertama Pada Kecelakaan (P3K) Di Sekolah Menengah Atas (SMA) Pangkah: Indonesia - Mutiarawati, Mutiarawati; Rahmanindar, Nora (LPPM Hang Tuah Pekanbaru, 2025)
Knowledge of First Aid (P3K) is crucial for students because schools are environments with a high risk of injury due to physical activity or medical emergencies. The 2018 Basic Health Research (Riskesdas) data recorded that 6.5% of injuries occurred in schools. First aid knowledge is not only crucial for saving lives but also for building safety awareness, preparedness, and social responsibility in students. First aid is an important initial step to prevent the victim's condition from worsening before receiving medical assistance. This type of quantitative descriptive research uses a cross-sectional design with a population of 645 students, namely 324 students in grade X and 321 students in grade XI. The sample was determined using the Slovin formula with a 5% error rate, resulting in 247 respondents. The sampling technique used proportional stratified random sampling because the population is stratified and not homogeneous. The research location is at SMA N1 Pangkah, the data collection technique used a Google Form-based questionnaire with a validity value of 0.75 and a Crombach Alpha reliability value of 0.82. This indicates that the consistency of the instrument is in the good category (α > 0.7). The results showed that the majority of respondents, both male and female, had a moderate level of knowledge about first aid, at 63.6%. Moderate knowledge dominated various first aid topics, such as the concept of first aid, fainting, choking, wounds and bleeding, broken bones, and bites and stings. However, the topic of food poisoning stood out with the highest level of low knowledge (70.9%). Overall, respondents' knowledge was quite good, but reinforcement of material on critical aspects of first aid that often occur in everyday life is needed. The conclusion of this study emphasizes the importance of further education and supporting facilities to improve adolescents' preparedness as first aiders in emergencies at school.